Knowledge, Attitude and Behavior of Dentists Toward Management of Special Needs Patients in Benghazi City - Elbagermi , Amal M M (Scientific Journal of University of Benghazi, 2020)
Background: Special needs patients (SNPs) are one of the underserved dental patient worldwide. A compromised oral health condition amongst SNPs has been associated with shortage of skills of dental professionals in management. Objective: to determine the level of knowledge, attitudes and behaviors of Libyan dentists towards caring for SNPs. Methods: A cross sectional study including Libyan dentist in public and private dental clinics in Benghazi. Data were collected from a representative sample by using a modified questionnaire. Results: In the total sample (234), 32.1% of participants were males and 67.9% were females. More than half of them lacking knowledge about dealing with severely mentally disabled patient while more than 63% of dentists know major barriers in treating SNPs and more than 66% of respondent consider lecture as main source of their knowledge about special care dentistry. Most of them do not believe that all mental disabled patients need sedation before treatment, majority of respondent believe that the communication between dentist and special needs patients will be effective in treatment, and most of dentists did not feel confident in providing care for them. 90.2% of respondent use non-pharmacological method of behavior control rather than sedation and general anesthesia .Around 90% of participants cannot manage mentally disable patients in their clinics with around 70% did not have the facilities for treating SNPs at their dental clinics. Conclusion: Dentists were lacking knowledge about dealing with severe mentally disabled patients, meanwhile they had a good knowledge regarding major barriers in treating SNPs. They had a positive attitude that they believe not all mental disabled patients need sedation before treatment and the communication between dentist and special needs patient will be effective in treatment while they had a negative attitude that they did not feel confident in providing care for them, they cannot manage mentally disable patients in their clinics. There is a good issues that dentists use of non-pharmacological methods to prepare them for dental visits.